The digital storytelling of Malaysian traditional games in preserving Malay heritage: a systematic review - Mohamad Jan, Intan Solehah; Che Din, Sharkawi (Universiti Teknologi MARA, Perak, 2025)
Traditional Malaysian games are a vital component of the nation's cultural heritage, reflecting identity, moral values, and communal practices. However, their relevance has declined due to the rise of modern digital entertainment and limited public awareness, especially among younger generations. This study examines the potential of digital storytelling (DST) as a medium for preserving and promoting traditional Malay games in a manner that resonates with contemporary audiences. It aims to explore the cultural value of these games and assess how DST, through visual and narrative-based formats, can support the promotion of Malay heritage. A Systematic Literature Review (SLR) was conducted following the PRISMA 2020 framework. Sixteen peer-reviewed articles published between 2010 and 2024 were selected based on defined inclusion and exclusion criteria. The findings revealed three key themes: (1) the cultural value of Malay traditional games (2) challenges in preserving traditional games and heritage, and (3) the role of digital storytelling in cultural promotion.